2008
DOI: 10.1093/annonc/mdm448
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin-6 as a tumor marker for hepatocellular carcinoma

Abstract: IL-6 could be considered a promising tumor marker for HCC. In particular, the diagnostic value of the test is significantly increased when combined with A(1)FP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
126
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(144 citation statements)
references
References 37 publications
15
126
2
1
Order By: Relevance
“…As in the gp130-deleted animals, no STAT3 DNA binding was found, and activation is likely to be mediated through a gp130-dependent cytokine while in IL-6 null animals, no STAT3 activation was found [63]. IL-6 levels in liver cancer patients are 25-fold higher than in healthy adults [64]. Subsequent studies showed that the levels of IL-6 in SNU-387 and SNU-449 liver cancer cell lines were much higher than those in human hepatocytes [65].…”
Section: Inflammationmentioning
confidence: 81%
“…As in the gp130-deleted animals, no STAT3 DNA binding was found, and activation is likely to be mediated through a gp130-dependent cytokine while in IL-6 null animals, no STAT3 activation was found [63]. IL-6 levels in liver cancer patients are 25-fold higher than in healthy adults [64]. Subsequent studies showed that the levels of IL-6 in SNU-387 and SNU-449 liver cancer cell lines were much higher than those in human hepatocytes [65].…”
Section: Inflammationmentioning
confidence: 81%
“…At a threshold of 7.9 pg/mL, inter leukin-6 (IL-6) has a sensitivity of 0.83, a specificity of 0.83, and an AUC of 0.810 [62] . Higher Creactive protein and IL6 levels correlated well with larger tumour sizes, poorer ChildPugh functions, shorter survival times and more predictable outcomes in patients with HCC receiving locoregional therapy [63] .…”
Section: Interleukin-6mentioning
confidence: 99%
“…Hep3B and SNU-398 cells were cultured in serumfree medium overnight and then were pre-treated with different concentrations of FLLL32 for 4 hours followed by 25 HCC patients than in healthy controls, whereas IL-6 receptor levels do not show much change. 9,10 Moreover, high serum IL-6 may promote HCC development in hepatitis B patients. 11 Thus, IL-6 could be considered a HCC biomarker and high risk factor for HCC.…”
Section: Flll32 Inhibits Il-6-induced Stat3mentioning
confidence: 99%